Public educational expenditure, costs and financing : an analysis of trends 1970-1988 - (:unkn) unknown (My University, 1992)
"The main purpose of this book is to assess the public effort in favour of education. Its focus is limited, therefore, to public resources spent on public and private formal education ... The study has been limited to two objectives: a) to undertake a thorough analysis of past trends in public expenditure on formal education in as many OECD countries as possible, depending on the availability of statistics, with a view to evaluating the overall trend as well as the trend by educational level; b) to review the existing mechanisms of public financing and explore the options available to governments and education authorities alike in complementing scarce public resources during a period of rising social demands." (author's abstract) ((en)) Die Studie zielt darauf ab, öffentliche Ausgaben für das formale Bildungswesen, Kosten und Finanzierung in OECD-Ländern für den Zeitraum 1970-1988 einzuschätzen. Kapitel 1 zeigt den allgemeinen Kontext auf, Kapitel 2 analysiert das Muster der gesamten öffentlichen Ausgaben für das Bildungswesen, Kapitel 3 zeigt die Entwicklung der Ausgaben nach Bildungsebenen. Kapitel 4 stellt öffentliche Hilfen für private Bildungseinrichtungen dar, Kapitel 5 befasst sich mit grundsätzlichen bestehenden und alternativen Modellen für Bildungsfinanzierung. (IAB)
Öffentliche Bildungsausgaben, Kosten und Finanzierung - Eine Trendanalyse 1970-1988
Keywords: S 4 Kosten & Finanzierung; S 1 Stufen der Berufsbildung; T 4.4 Politikwissenschaften; Finanzierung; Ausgaben; Bildungssystem; Kosten; Staat; Bildungsinvestition; Internationaler Vergleich; Quantitative Angaben; OECD